Web based GIS for asset location detection - Mohammad Zulfikri, Omar (2006)
The Web based GIS for Assets Location System has been developed for Office of Development & Asset Management (PPH) to trace the assets in Kolej Universiti Kejuruteraan dan Teknologi Malaysia (KUKTEM).The system was built due to the current problem that arises from the Asset Tagging System that currently used by the PPH.The problem from the existing system is user cannot collect asset data for particular location.Because of this weakness this project is developed. The system is applying GIS technique to overcome the current situation.This technique can give a new version to user on accessing data in an interactive way in KUKTEM area.The usage of this system provide few function such as Zoom to Full Extend,Zoom to Active Theme,Zoom Out,Zoom In,Pan and search function which could help identifYing of asset location process within a department.The success of implementation and development of this project is expected to help in reducing human power in allocate an asset.